Study of the Catalytic Kinetic Spectrophotometry of Iron(III)-(Dibromo-p-methyl-arsenazo)-Potassium Bromate - Hu, Wei-Hua; Zhai, Qing-Zhou; Lin, Xue (Asian Journal of Chemistry, 2012)
Trace amount of iron is a necessary element for human body. The iron content in some foods is not only high, but also the absorption rate is high. To the anemia patient of lacking iron, it is of great benefit. It can also prevent heart disease and lower the role of cholesterol. Therefore, the research of new method for the determination of trace amount of iron has applied value. In a sulfuric acid medium of 5 × 10-3 mol L-1, the maximum absorption wavelength of Fe(III)- (dibromo-p-methyl-arsenazo)-KBrO3-ascorbic acid system is at 530 nm. The amount of iron(III) over the range of 0.5-7.0 ng/mL and the difference of absorbance present a good linear relationship. The detection limit of the method is 0.26 ng mL-1. The present method was satisfactorily applied to the determination of trace iron in peanut.